Biosynthesis of biobutanol from oil palm frond juice by Clostridium acetobutylicum - Nur Syazana, Muhamad Nasrah (2019)
Energy from biomass resources is becoming increasingly important, since it can be used to partly displace conventional sources of energy. The Malaysian oil palm industry generates huge quantities of lignocellulosic biomass which created a major disposal problem. Therefore, oil palm frond (OPF) juice was introduced as a substrate in Acetone-Butanol-Ethanol (ABE) fermentation to produce biobutanol by Clostridium acetobutylicum ATCC 824. This study aims to investigate the potential of OPF juice as a substrate for the butanol production. During preliminary study, the production in OPF juice was compared with synthetic sugar as control experiment. Next, this study proceeds with the second and third objective to screen and optimize the factors affecting ABE fermentation by C. acetobutylicum ATCC 824. Sugar content in OPF juice was determined to identify the initial sugar concentration for the fermentation. Response Surface Methodology (RSM) was employed to screen and optimize the butanol production. The total sugar analyzed using High Performance Liquid Chromatography (HPLC) in OPF juice was 68.58 g/L, with glucose, sucrose and fructose value 48.19 g/L, 8.48 g/L and 11.91 g/L, respectively. The culture produced 9.24 g/L of biobutanol using OPF juice with 0.24 g/g biobutanol yield. Meanwhile, 10.91 g/L biobutanol produced using synthetic sugars as control experiment with 0.27 g/g biobutanol yield. The biobutanol yield produce by synthetic sugar in control experiment seem comparable to the fermentation in OPF juice, with only 11.25% higher than OPF juice. In factorial analysis, yeast extract concentration was the highest factor affecting the fermentation process with 8.20% contribution. The second and third highest contribution factors was inoculum size and incubation temperature. These three factors were then optimized using RSM. The optimum condition of the fermentation was found out at 10% inoculum size, 37°C incubation temperature and 5.5 g/L yeast extract concentration which 0.2992 g/g biobutanol yield was obtained in validation process. These experimental findings were in close agreement with the model prediction, with a difference only 9.76%. Overall, ABE fermentation to produce biobutanol using OPF juice by C. acetobutylicum ATCC 824 has high potential which later can be used as commercial substrate in biofuel industry.